The Influence of Social Capital on the Participation of Farmer Group Members in the Rice Barn Program in Pendem Village, Junrejo District, Batu City - Fadhila Hasna; Ari, Ismu Rini Dwi; Nugroho, Salma Fitri; Ula, Aisyah Nabilatul; Nurrohma, Laiza Afi (Journal of Regional and Rural Studies, 2026)
This study examines the relationship between social capital and farmer group members' participation in the Rice Barn Program in Pendem Village, Junrejo District, Batu City, East Java, Indonesia, a community-based food security initiative encompassing irrigation management, agricultural extension, and post-harvest processing. A quantitative cross-sectional survey was conducted from January to March 2025, involving 193 farmer group members selected through accidental sampling from a population of 386. Data were collected via structured questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Confirmatory Factor Analysis confirmed that social capital was validly represented by three dimensions, trust, social norms, and social networks, after removing two low-loading network indicators, with all constructs meeting convergent validity (AVE > 0.50) and reliability (CR > 0.70) criteria. SEM results showed that social capital was positively and significantly associated with farmer participation (β = 0.456; t = 7.319; p < 0.001), explaining 69.2% of the variance in participation (R² = 0.692). Trust emerged as the strongest contributing dimension, followed by social networks and social norms. These findings indicate that stronger social capital, particularly trust-based relationships, enhances farmer participation in village-based agricultural development programs. This study contributes empirical and methodological insights into social capital's role in participatory rural food security, including clarification on interpreting path coefficients, R², and effect size (f²) in PLS-SEM analysis.